Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Tax Avoidance - Kenedi Pratama; Meri Yani (Jurnal Literasi Akuntansi, 2026)
Purpose : This research aims to determine whether profitability, leverage, and company size affect tax avoidance Method : The research method used is a quantitative method. The population in this study consists of primary consumer goods companies listed on the Indonesia Stock Exchange from 2015 to 2018. The sampling technique used in this study is purposive sampling, with a sample size of 54 data points. The data analysis methods used are descriptive analysis, classical assumption tests, and hypothesis testing, using SPSS software. Finding : The test results show that: 1) Based on the t-test, it is known that the profitability variable affects tax avoidance. 2) Based on the t-test, it is known that the leverage variable affects tax avoidance. 3) Based on the t-test, it is known that the company size variable affects tax avoidance. 4) Based on the F-test, it is known that the variables of profitability, leverage, and company size affect tax avoidance. Novelty : This study focuses on primary consumer goods companies listed on the Indonesia Stock Exchange during the 2015–2018 period, by integrating three key variables, profitability, leverage, and firm size into a single comprehensive framework. This approach differs from previous studies that generally analyzed tax avoidance across various industries or examined each variable separately in conjunction with different moderating or control factors, without emphasizing a specific industrial context or time frame.